Growing in Asia: P&G turns to market research - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
“Create excitement in the market with new products; entice the competitors to play, and together, we can grow the market,” said Medhee Jarumaneeroj, the 'influencer marketing & external relations leader' for Procter & Gamble (P&G) Asia's male grooming outfit. Speaking at the Marketing Excellence Speaker Series, a monthly talk organised by SMU's Centre of Marketing Excellence, Jarumaneeroj expressed excitement about Asia as a huge growth market for the American multinational.